THE MEDIATING ROLE OF ORGANIZATIONAL LEARNING IN THE RELATIONSHIP BETWEEN LEADERSHIP COMMUNICATION, KNOWLEDGE MANAGEMENT, AND ORGANIZATIONAL COMMITMENT AMONG ACADEMICIAN IN CHINESE HIGHER EDUCATION INSTITUTES - ZhengKang, Fang; Mohd Yaakob, Mohd Faiz; Yeap, Sock Beei (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study investigates the mediating role of organizational learning (OL) in the relationship between leadership communication (LC), knowledge management (KM), and organizational commitment (OC) among academic staff in Chinese higher education institutions. Using a cross-sectional survey design, data were collected from 402 academic staff and analyzed through partial least squares structural equation modeling (PLS-SEM). The model tested the direct effects of LC and KM on OL and their subsequent impact on OC. The results reveal that LC significantly influences OL (B = 0.615, p < 0.001), while KM also has a positive and significant effect on OL (B = 0.203, p < 0.001). OL, in turn, plays a crucial role in enhancing OC (B = 0.754, p < 0.001). Importantly, OL mediates the relationship between LC and OC (B = 0.464, p < 0.001) and between KM and OC (B = 0.153, p < 0.001). The model demonstrated high explanatory power, with OL accounting for 70.2% of its variance (R² = 0.702) and OC explaining 58.5% (R² = 0.585). This research uniquely integrates OL as a mediator in the triadic relationship between LC, KM, and OC, offering new insights into how organizational learning strengthens organizational commitment. It enriches the underexplored context of Chinese higher education and provides practical recommendations for academic leaders and policymakers. By fostering a learning-centric environment, institutions can enhance knowledge-sharing practices, improve communication strategies, and build long-term organizational loyalty among academic staff.